Molecular Mechanisms That Contribute to Horizontal Transfer of Plasmids by the Bacteriophage SPP1 - Valero-Rello, Ana; López-Sanz, María; Quevedo-Olmos, Alvaro; Sorokin, Alexei; Ayora, Silvia (Frontiers in Microbiology, 2017)
Natural transformation and viral-mediated transduction are the main avenues of horizontal gene transfer in Firmicutes. Bacillus subtilis SPP1 is a generalized transducing bacteriophage. Using this lytic phage as a model, we have analyzed how viral replication and recombination systems contribute to the transfer of plasmid-borne antibiotic resistances. Phage SPP1 DNA replication relies on essential phage-encoded replisome organizer (G38P), helicase loader (G39P), hexameric replicative helicase (G40P), recombinase (G35P) and in less extent on the partially dispensable 5’→3’ exonuclease (G34.1P), the single-stranded DNA binding protein (G36P) and the Holliday junction resolvase (G44P). Correspondingly, the accumulation of linear concatemeric plasmid DNA, and the formation of transduction particles were blocked in the absence of G35P, G38P, G39P and G40P, greatly reduced in the G34.1P, G36P mutants, and slightly reduced in G44P mutants. In contrast, establishment of injected linear plasmid DNA in the recipient host was independent of viral-encoded functions. DNA homology between SPP1 and the plasmid, rather than a viral packaging signal, enhanced the accumulation of packagable plasmid DNA. The transfer efficiency was also dependent on plasmid copy number, and rolling-circle plasmids were encapsidated at higher frequencies than theta-type replicating plasmids.